The 5 g. d-xylose absorption test - Joske, R. A. (1964)
The 5 g. d-xylose absorption test has been studied in 50 normal subjects. The five-hour urinary xylose content was 1·75 ± 0·43 g. Xylose absorption was more rapid and more complete with the 5 g. than with the 25 g. test. Comparative studies showed the results of the two tests to be significantly related, but the 5 g. test was a less sensitive indicator of malabsorption than the 25 g. test. The 25 g. test is considered the more suitable for routine use in temperate climates.